(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective(s): The aim of this study is to evaluate frequency and nature of maternal deaths and maternal near-miss cases in a tertiary care hospital. Materials and Methods: A retrospective examination was conducted on records of the16.612 women who delivered in a tertiary care center, over a ten-year period (1997-2006). The flow chart recommended by Say et al was used in the analysis of the maternal near-miss cases. Results: The ratios of mortality related with pregnancy, maternal mortality and maternal nearmiss were 68.11/100.000, 61.29/100.000 and 17.09/1000, respectively. The ratio of maternal near- miss to maternal mortality was 27.8 and the mortality index was 3.46%. Hypertensive disorders were the leading cause of maternal deaths and maternal near-miss events. Conclusion: Hypertensive disorders were still leading cause of maternal deaths and maternal near-miss events.Absence of antenatal care and disrupted referral chains were major problems. Bangladesh J Obstet Gynaecol, 2015; Vol. 30(2) : 92-97